The corporate social responsability: focusing on consulting/advisory, banking and retail business sectors - Pereira, Patrícia Alexandra Justino (2020)
The Corporate Social Responsibility (CSR) theme has increasingly debated, reaching greater relevance in the society in which we are living. This thematic is frequently present in the policies and decisions of managers in the organizations they are leading, namely in the three main dimensions, economic, social, and environmental, due to the change and demands that society imposes. However, there is still a devaluation of workers' opinions regarding the implementation of CSR policies by managers who oversee decision making. In that way, this study was based on a literature review to understand the critics’ opinions of this theme. Then, a survey was applied to workers who currently are working in consulting companies, in the banking area, or retail companies, and the data was submitted to quantitative treatment. The focal objective of this survey was to understand the importance that workers give to the practice of CSR policies and what impact these actions would have on the organization by employees’ perspective. The results indicated that the employees, regardless of the industry which they are working for, considered that the implementation of good CSR policies is an added value for the employee if they are consistent with his needs. Regarding questions related to the impact of these practices would have on the organization, all respondents agree that the implementation of these policies can meet the needs of workers and maximize the reputation of the organization. Still, around 91% of the respondents acknowledge that good CSR practices could improve companies' financial performance and profitability by providing quality goods and services.